Brief note on Food systems and the role of livestock - Kassie, Girma T. (International Center for Agricultural Research in the Dry Areas, 2022)
Brief note on Food systems and the role of livestock presentation in “Contribution of Livestock to the Food Systems Transformation in Ethiopia”. Hawassa, Ethiopia. September 15-17, 2022.